Re-evaluation of earthquake performance and strengthening alternatives of Hagia Sophia - Kırlangıç, Ahmet Serhan. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2008., 2008)
Static and dynamic linear analyses were carried out to evaluate the structural behaviour of and to propose strengthening strategies for Hagia Sophia. A Finite Element model of the structure was used for this purpose. While linear static self-weight and eigenvalue analyses were performed to ensure that the finite element model represents the structure, response spectrum analysis was used to obtain the deformation and stress distributions for determining the regions where intervention is needed. Response spectrum analysis revealed that main arches, semidomes and domebase exhibit high stress concentrations. These particular elements were the target zones for intervention. Two main strengthening strategies were considered: i) Retrofitting the main arches with post-tensioned bars, ii) Wrapping the structural elements with fiber reinforced polymers FRPs. These two strategies were modelled and changes in the structural behaviour were observed. The analyses revealed post-tensioning as a more effective approach as compared to wrapping the structural elements with FRP laminates.
Keywords: Historic buildings -- Turkey -- Conservation and restoration.; Buildings -- Earthquake effects.; Historic buildings -- Protection -- Turkey.